Relations of Intellectual Capital Components in Hotel Companies - Ognjanovic, Jasmina M. (Industrija, 2017)
As an invisible asset within a company, in achieving the impact on business processes, intellectual capital uses its three components – human capital, structural capital and relational capital. The aim of the paper is to examine the interdependence between the aforementioned intellectual capital components. The research combines factor analysis and structural equation modelling on a sample of 44 hotel companies in Serbia. The results indicate the presence of a strong and positive relationship between the observed IC components. The strongest relationship is observed between relational capital and structural capital. Factor analysis confirmes grouping of the defined criteria around three factors - human, structural and relational capital.